(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
It is given a local presentation of strategies of theoretical annihilation of subject of creativity, which, as we know, inspired the redefining of author’s category in the theoretical and methodological, historical and literary studies of modern Ukrainian scientists.